KUALITAS HADIS SHAHIH, HASAN, DHAIF SEBAGAI HUJJAH DALAM HUKUM ISLAM - Wahab, Fatkhul (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
As the second source of Islamic law after the Qur'an, Hadith is divided into three, namely Sahih, Hasan and Dhaif Hadith. Sahih hadith is a hadith that fulfills the conditions: Sanad hadith is continuous, the narrator is fair, dhabith, not syadz and safe from 'illat. Hasan Hadith is a hadith that has the following criteria: Sanad is continuous, the transmitter is fair. dlabith, not syadz and not violating the history of more tsiqah narrators. Dhaif hadith is a hadith that does not meet the requirements of qabul. This is due to: Defects in the narrator and the discontinuity of the sanad. On this basis, this research was conducted with a focus on: What is the position of Sahih, Hasan, Dhaif Hadith as Hujjah in Islamic Law? This research is a literature study with a qualitative descriptive approach using the Content Analysis method. The findings in this study are the practice of Sahih, Hasan and Dhaif Hadith. Scholars agree that the Hadith Sahih and Hasan must be practiced except according to Imam Bukhari and Ibn 'Arabi, Hasan Hadith cannot be practiced. Meanwhile, there are 3 madzhabs of Dhaif Hadith: (1) It is permissible to practice absolutely, both in fadhail a'mal, and in Shari'a law with the condition that the daif is not a dhaif syadid, (2) It is permissible to practice in terms of fadhail a'mal, zuhud, advice, stories -the story, apart from sharia law and creed, as long as the hadith is not a maudu hadith, (3) it is not permissible to practice a daif hadith absolutely.